PESAN VERBAL DALAM KOMUNIKASI ANTARBUDAYA - Ismuhar, Ismuhar (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2019)
Verbal messages in intercultural communication using qualitative methods with a phenomenological approach. In the current era of globalization, the rapid development of information and communication technology has provided opportunities to communicate with someone who speaks a different language and culture. The main obstacle in intercultural communication is cultural differences and language problems. Cultural differences often make communication ineffective. Cultural differences can be demonstrated in social values, status ideas, decision-making habits, attitudes toward time, distance setting, cultural context, body language, customs, legal behavior and ethics. There are several ways that can be taken to overcome communication problems that arise due to diversity and cultural change, namely through: Assimilation, self-segregation is that each party separates and avoids each other in order to reduce tension. Then integration and pluralism.